METAKOGNISI SISWA DENGAN GAYA BELAJAR INTROVERT DALAM MEMECAHKAN MASALAH MATEMATIKA - Marni Zulyanty; Ipung Yuwono; Makbul Muksar (FMIPA UNIVERSITAS NEGERI MALANG, 2017)
One of the most important aspects of mathematic learning is mathematical problem solving. The importance of mathematical problem solving in Indonesia is reflected in the graduate competency standards of curriculum. The competence underlined awareness and control over cognitive process in solving a problem often called as metacognition. This research titled “students’ introvert learning style metacognitive in solving mathematical problems” aimed to describe introvert students’ metacognitive ability to solve problem, as a variant of learning styles. This is a qualitative research with introvert learning style students as the subject. The research concludes that students with introvert learning style have used high level metacognition in solving mathematical problem.